Blood and oil : the dangers and consequences of America's growing petroleum dependency - Klare, Michael T., 1942- (New York : Metropolitan Books/Henry Holt & Co., 2004)
Since September 11th and the commencement of the "war on terror," the world's attention has been focused on the relationship between U.S. foreign policy in the Middle East and the oceans of crude oil that lie beneath the region's soil. Klare traces oil's impact on international affairs since World War II, revealing its influence on the Truman, Eisenhower, Nixon, and Carter doctrines. He shows how America's own wells are drying up as our demand increases by 2010, the United States will need to import 60 percent of its oil. And since most of this supply will have to come from chronically unstable, often violently anti-American zones-the Persian Gulf, the Caspian Sea, Latin America, and Africa-our dependency is bound to lead to recurrent military involvement.
With clarity and urgency, Blood and Oil delineates the United States' predicament and cautions that it is time to change our energy policies, before we spend the next decades paying for oil with blood.--from the publisher
1. The dependency dilemma: imported oil and national security -- 2. Lethal embrace: the American alliance with Saudi Arabia -- 3. Choosing dependency: the energy strategy of the Bush administration -- 4. Trapped in the Gulf: the irresistible lure of bountiful petroleum -- 5. No safe heavens: oil and conflict beyond the Persian Gulf -- 6. Geopolitics reborn: the U.S.-Russian-Chinese struggle in the Persian Gulf and Caspian Basin -- 7. Escaping the dilemma: a strategy for energy autonomy and integrity.
Includes bibliographical references and index.
Keywords: Petroleum industry and trade -- United States; Energy policy -- United States; National security -- United States